2019
DOI: 10.1029/2019gl082666
|View full text |Cite
|
Sign up to set email alerts
|

Shift in the Temporal Trend of Boundary Layer Height in China Using Long‐Term (1979–2016) Radiosonde Data

Abstract: The knowledge regarding how the boundary layer height (BLH) changes over time is still poor. Here we analyze the spatial and temporal changes in radiosonde‐derived measurements of BLH over China from 1979 to 2016. A qualitatively robust and abrupt change of BLH occurred in 2004. Over the former period (from 1979 to 2003) a spatially uniform increase was found in the BLH, while over the latter period BLH decreased in a spatially nonuniform way. Second, the meteorological influence on the rising BLH was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 147 publications
(100 citation statements)
references
References 61 publications
6
93
1
Order By: Relevance
“…Interestingly, radiosonde‐derived BLHs have shown a trend reversal (from increasing to decreasing) in recent decades in China. This is found, however, to be correlated more with increases in soil moisture than with the aerosol trend (Guo et al, ). Therefore, the long‐term impact of ADR, especially on the PBL structure, remains inconclusive and merits further analyses by combining observations with model simulations where land‐atmosphere coupling should be considered.…”
Section: Aerosol Formation Nucleation Optical Properties and Radiamentioning
confidence: 99%
“…Interestingly, radiosonde‐derived BLHs have shown a trend reversal (from increasing to decreasing) in recent decades in China. This is found, however, to be correlated more with increases in soil moisture than with the aerosol trend (Guo et al, ). Therefore, the long‐term impact of ADR, especially on the PBL structure, remains inconclusive and merits further analyses by combining observations with model simulations where land‐atmosphere coupling should be considered.…”
Section: Aerosol Formation Nucleation Optical Properties and Radiamentioning
confidence: 99%
“…Moreover, it is also noted that during the process of dust transport, dry‐and‐wet depositions are nonnegligible factors influencing the dust loading in the downstream regions (Dai et al, ; Guo et al, ; Yim et al, ). Interestingly, soil moisture in China has shown to be experiencing significant increasing trend in recent decade (Guo et al, ), which could be due to the fast greening speed through land use management in this region (C. Chen, Park, et al, ). Therefore, the changes in soil moisture should also be taken into account when analyzing the long‐term trend of dust over East Asia and the North Pacific Ocean (EA&NPO).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of climate change effects predicted by the Intergovernmental Panel on Climate Change scenarios indicated that Brazilian urban populations are likely to become more exposed to the adverse urban effects such as significant reduction on precipitation and augment in temperature (Batista et al, ; Lyra et al, ). On the other hand, long‐term variation of PBL height carried out in Europe, China, and Japan (Guo et al, ; Zhang et al, ; Zhang & Li, ) indicated that there is an overall tendency to increase the PBL height as a response to the global warming, mainly increase in the surface temperature and reduction in the relative humidity. However, it is still not possible to infer what would be the impact of the Intergovernmental Panel on Climate Change scenarios on the PBL heights over urban areas.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%